Implementasi Pendidikan Soft Skills dalam Membentuk Moralitas Siswa di Madrasah Aliyah Negeri Bangkalan - Husairi, Husairi; Rachman, Lutfi (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2021)
The education is called as student character development process so that students have the knowledge (cognitive), attitudes (affective) and skills (psychomotor) for the provision of living the midst of society. This process involves improvement the intellectual, personal and social skills are balanced between hard skills and soft skills that are not only useful for himself (intrapersonal skills) but also beneficial to the existence of society (interpersonal skills). Soft skills are a core part of non-technical competencies that are specifically able to refer to personality characteristics. These competencies are seen in a person's behavior, starting when interacting with the social environment, language skills, personal habits, to important traits aimed at supporting optimistic behavior in all fields. The characteristics of the educational model of soft skills in forming morality of students in Madrasah Aliyah Negeri Bangkalan that is using a model of